2017
DOI: 10.1007/s12639-017-0919-1
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of gastrointestinal nematodes in goats in and around Mhow, Madhya Pradesh

Abstract: Gastrointestinal (GI) parasitism in animals is considered as one of the major problems in India causing recurring economic losses to livestock production system owing to morbidity and mortality. But data pertaining to epidemiology of GI nematodes in goats is meager from Malwa region of Madhya Pradesh. Therefore, the present investigation was carried out to study the incidence of GI nematodes in goats in and around Mhow and accordingly a total of 900 faecal samples of goats were collected from Mhow and its adjo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…Based on the observation conducted in the two villages during the rainy and dry seasons, GI parasite infections in thin-tailed sheep were higher than those in Wonosobo sheep in the two villages. The infection rate in the rainy season was observed to be higher in this study than that in the dry season, agreeing with the results reported by Velusamy et al [33], Das et al [34], Shakya et al [35], Kanojiya et al [36], Gul and Hidayatullah [37], and Dixit et al [38]. Given that Wonosobo sheep have been raised in Indonesia since 1957, it is expected that they have adapted to the region.…”
Section: Discussionsupporting
confidence: 91%
“…Based on the observation conducted in the two villages during the rainy and dry seasons, GI parasite infections in thin-tailed sheep were higher than those in Wonosobo sheep in the two villages. The infection rate in the rainy season was observed to be higher in this study than that in the dry season, agreeing with the results reported by Velusamy et al [33], Das et al [34], Shakya et al [35], Kanojiya et al [36], Gul and Hidayatullah [37], and Dixit et al [38]. Given that Wonosobo sheep have been raised in Indonesia since 1957, it is expected that they have adapted to the region.…”
Section: Discussionsupporting
confidence: 91%
“…Many LMICs have extreme or highly variable climates, including monsoons, tropical humidity, and severe heat. During monsoon seasons, heavy rainfalls combined with inadequate shelter promote hoof disease and infections (Chakrabarti & Kumar, 2016), parasites and other disease vectors (Dappawar et al, 2018;Khajuria et al, 2013;Muraleedharan, 2005;Shakya et al, 2017), and mastitis in cattle and buffalo (Khan et al, 2015;Singh et al, 2021). Condition issues are often exacerbated in commercial and exotic breeds, which have been bred for temperate or highly controlled environments, and high-input production systems (Nielsen & Zhao, 2012).…”
Section: Animal Welfare Priorities In Lmics and The Potential For Gen...mentioning
confidence: 99%
“…India accounts for the largest livestock sector in the world, with goat farming contributing to 26.40% of the sector and thus playing a key role in the rural economy [1]. Gastrointestinal (GI) disorders are one of the important challenges affecting the profitability of goat husbandry practices in most countries, including India [2]. They lead to high mortality and morbidity rates, suboptimal productivity, increased sensitivity to diseases, banning of carcasses and organs, poor general health conditions, retarded growth, and high costs associated with preventive measures and veterinary aids [3].…”
Section: Introductionmentioning
confidence: 99%